Combustion acceleration in Al/CuO nanothermite films via gap-induced particle-advection mechanism - Xiaoxia Ma; Changcheng Bao; Lin Shi; Junzhe Xu; Wei Liu; Jimin Han; Li Yang (Chemical Engineering Journal, 2026)

Threshold-governed insulating and cooling effects of snow cover on alpine permafrost: evidence from the Qinghai–Tibet Plateau - Yao Xiao; Guojie Hu; Ren Li; Tonghua Wu; Xiaodong Wu; Guangyue Liu; Defu Zou; Zanpin Xing; Jimin Yao; Chong Wang; Lin Zhao (Agricultural and Forest Meteorology, 2025)

Local defect structure design enhanced energy storage performance in lead-free antiferroelectric ceramics - Peixuan Li; Simin Wang; Jin Qian; Guanglong Ge; Luomeng Tang; Jinfeng Lin; Weiwei Yang; Jimin Lin; Weikang Lin; Bo Shen; Jiwei Zhai (Chemical Engineering Journal, 2024)

The skin photoprotective effect of trilinolein: Induction of cellular autophagy via the AMPK-mTOR signaling pathway - Xianghong Lin; Na Deng; Huijuan Li; Jingxian Duan; Wenqiu Chen; Tao Liu; Sujiao Sun; Jimin Chu (Toxicology and Applied Pharmacology, 2024)

Spatio-temporal variation in soil thermal conductivity during the freeze-thaw period in the permafrost of the Qinghai–Tibet Plateau in 1980–2020 - Liu Wenhao; Li Ren; Wu Tonghua; Shi Xiaoqian; Wu Xiaodong; Hu Guojie; Zhao Lin; Yao Jimin; Wang Dong; Xiao Yao; Shi Jianzong; Ma Junjie; et al. (Science of The Total Environment, 2024)

The spatiotemporal variations of freezing index and its relationship with permafrost degradation over the Qinghai–Tibet Plateau from 1977 to 2016 - Ren Li; Junjie Ma; Tonghua Wu; Qinxue Wang; Xiaodong Wu; Lin Zhao; Shenning Wang; Guojie Hu; Wenhao Liu; Yongliang Jiao; Jimin Yao; Yao Xiao; et al. (Theoretical and Applied Climatology, 2024)

A study of land use changes and its impacts on flood inundation in the Konkoure River Basin, Republic of Guinea - Alhassane Bah; Hongbo Zhang; Zhumei Luo; Jimin Hu; Zulian Zhang; Yang Lin Xie; Ting Yang; Guohong Chen; Alseny Bah (Environmental Monitoring and Assessment, 2024)

Approaches to assessing the daily average ground surface soil heat flux on a regional scale over the Qinghai-Tibet Plateau - Cheng Yang; Tonghua Wu; Guojie Hu; Xiaofan Zhu; Jimin Yao; Ren Li; Lin Zhao; Yinghui Zhang (Agricultural and Forest Meteorology, 2023)

Cold spells linked with respiratory disease hospitalization, length of hospital stay, and hospital expenses: Exploring cumulative and harvesting effects - Jin Feng; Dawei Cao; Dashan Zheng; Zhengmin (Min) Qian; Cunrui Huang; Huiqing Shen; Yi Liu; Qiyong Liu; Jimin Sun; Guangyuan Jiao; Xiaoran Yang; Stephen Edward McMillin; et al. (Science of The Total Environment, 2023)

Estimation of surface energy fluxes in the permafrost region of the Tibetan Plateau based on in situ measurements and the surface energy balance system model - Jimin Yao; Lianglei Gu; Cheng Yang; Hao Chen; Jiemin Wang; Yongjian Ding; Ren Li; Lin Zhao; Yao Xiao; Yongping Qiao; Jianzong Shi; Caiping Chen (International Journal of Climatology, 2020)
The surface energy balance is a key issue in land surface process research and important for studies of climate and hydrology. In this paper, the surface energy fluxes (net radiation, ground heat flux, sensible heat flux and latent heat flux) at the Tanggula (TGL) and Xidatan (XDT) sites were measured and the distributions of the regional surface energy fluxes on the Tibetan Plateau were obtained using a revised surface energy balance system (SEBS) model. The results show that the surface energy fluxes have obvious seasonal variations. At both sites, the sensible heat flux is highest in spring and lowest in summer, and the latent heat flux is highest in summer and lowest in winter. The high elevation, snow cover, freeze–thaw process, precipitation, vegetation and soil texture are important influencing factors for land surface energy fluxes. The time‐phase difference between the net radiation and ground heat flux for bare soils is estimated to be 2–3 hr. The ratio of ground heat flux and net radiation ranged from approximately 0.18 to 0.33, and a parameterization scheme for the remote sensing of ground heat flux over the Tibetan Plateau bare soil in summer is developed. The simulation results of the regional surface energy fluxes show that the distributions of surface parameters, such as vegetation, soil texture and soil moisture content, are important for understanding regional changes in the surface energy fluxes.

Filtered maximum likelihood expectation maximization based global reconstruction for bioluminescence tomography - Defu Yang; Lin Wang; Dongmei Chen; Chenggang Yan; Xiaowei He; Jimin Liang; Xueli Chen (Medical & Biological Engineering & Computing, 2018)

Detection of spotted fever group Rickettsiae in ticks from Zhejiang Province, China - Jimin Sun; Junfen Lin; Zhenyu Gong; Yue Chang; Xiaodong Ye; Shiping Gu; Weilong Pang; Chengwei Wang; Xiaohua Zheng; Juan Hou; Feng Ling; Xuguang Shi; et al. (Experimental and Applied Acarology, 2015)